The Influence Of Celebrity Endorsers On Social Media Instagram On Buying Interest In Avoskin - Alvionita, Audy; Tantra, Tarandhika (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
It is estimated that the beauty product sector will continue to experience growth every year, especially in the skin care category which has become the most popular. In fact, Avoskin's achievement in becoming one of the best-selling skin care brands in ecommerce demonstrates this trend. This study aims to evaluate the effect of Celebrity Endorser on the Instagram social media platform on the intention to buy Avoskin products. There are three dimensions to the Celebrity Endorser variable, namely attractiveness, trustworthiness, and expertise. This study aims to identify whether there is a positive and significant effect of Celebrity Endorsers on Instagram on the intention to buy Avoskin products, and to consider the influence of each dimension. This type of research is quantitative and descriptive. Primary data was collected by distributing questionnaires via Google Form to 385 respondents. Based on the results of simultaneous hypothesis testing, the use of Celebrity Endorser on Instagram social media has a significant effect on Avoskin's purchase intention. This is evidenced by the value of Fcount (43,042) Ftable (3.089) with a significance level of 0.000 0.05. Based on the results of partial hypothesis testing (t test) it is found that the attractiveness, trustworthiness, and expertise variables have a significant effect on Avoskin's buying interest. Based on the coefficient of determination, it is found that celebrity endorsers are able to explain buying interest by 59% and the remaining 41% is explained by other factors outside the research variables. In this study, the variable trustworthiness was obtained as the variable with the highest value. It is necessary to emphasize the value of honesty in Celebrity Endorsers because it has a high influence on consumer buying interest